Association between low concentrations of antibodies to protein α and Rib and invasive neonatal group B streptococcal infection. Issue 6 (20th October 2006) - Larsson, C; Lindroth, M; Nordin, P; Stålhammar-Carlemalm, M; Lindahl, G; Krantz, I
Abstract : Background: Infection with group B streptococci (GBS) is a serious neonatal disease. The GBS cell surface proteins α and Rib elicit protective immunity in animal models and have been suggested as potential antigens in a vaccine against human GBS disease. Aims: To test the hypothesis that transplacentally transferred maternal antibodies to GBS proteins contribute to the protection of the neonate from GBS infection. Methods: Thirty neonates with invasive infection were included in a case-control study. IgG antibody concentrations were measured in sera from these neonates, their mothers, and from 60 non-infected controls, neonates as well as mothers. Results: A clear association was found between concentrations of antibody to proteins α and Rib in neonatal and maternal sera, indicating that transplacental transfer had occurred. Moreover, low concentrations of antibodies to α and Rib in neonatal sera were associated with invasive GBS infection caused by strains expressing the Rib protein. The odds ratio was 0.0007 (95% confidence interval 0.000 to 0.54) for antibodies to α and 0.002 (95% confidence interval 0.000 to 0.57) for antibodies to Rib. Conclusion: These findings support the notion that antibodies to GBS surface proteins contribute to the protection against neonatal infection.